Penyuluhan Terhadap Pengetahuan Ibu Hamil Dalam Teknik Menyusui Di Wilayah Kerja Puskesmas Singgani Kota Palu - Irmawati; Rajma (Jurnal Bidan Cendrawasih Palu, 2019)
The success of breastfeeding must begin with sensitivity to the right time when breastfeeding. Failure is usually caused by improper technique and position not because of the little milk production, the correct breastfeeding technique is one of the factors that influence the success of breastfeeding. The effort to increase the knowledge of pregnant women about breastfeeding techniques is to provide counseling. Health education is a learning process to develop a correct understanding and a positive attitude from individuals or groups to the health concerned has a healthy way of life as part of their daily way of life for their own awareness and willingness. The research objective was to know the effect of counseling on the knowledge of pregnant women in breastfeeding techniques in the Working Area of ​​the Singgani Health Center in the City of Palu. This study is a type of analytical research with a cross sectional approach. The population in this study were all pregnant women in the Singgani Health Center Working Area. The sample of this study was 43 respondents, the sampling technique was accidental sampling. The analysis used in this study is univariate and bivariate analysis. The results showed that from 43 respondents, most of the mothers before counseling had good knowledge of 55.82% and mothers who had poor knowledge 34.88%. After counseling, the average mother has good knowledge (95.35%). The results of the "Wilcoxon" test p value: <0.01 (0,000 <0.01). The conclusion is the influence of counseling on the knowledge of pregnant women in breastfeeding techniques at the Singgani Health Center.